2016
DOI: 10.5812/jjm.30682
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biofilm Formation Among Klebsiella pneumoniae Isolates and Molecular Characterization by ERIC-PCR

Abstract: Background:Klebsiella pneumoniae is among the most frequently recovered etiologic agents from nosocomial infections. This opportunistic pathogen can generate a thick layer of biofilm as one of its important virulence factors, enabling the bacteria to attach to living or abiotic surfaces, which contributes to drug resistance.Objectives:The resistance of biofilm-mediated infections to effective chemotherapy has adverse effects on patient outcomes and survival. Therefore, the aim of the present study was to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
65
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 31 publications
15
65
1
2
Order By: Relevance
“…However, biofilm formation in our study was also observed in high rate in the isolates obtained from other specimens: 83.3%, 71.7% and 66.6% of isolates from pus, urine and sputum, respectively. Our observations were close to those of Seifi et al [15] who also reported that K. pneumoniae isolated from urine, sputum, blood and wound swabs were able to produce biofilm. Detection of biofilm formation even in the isolates originated from OPDs in the present study indicates that K. pneumoniae has the capacity to form biofilm not only on the medical devices used in the hospitalized patients but also directly on the host tissues.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, biofilm formation in our study was also observed in high rate in the isolates obtained from other specimens: 83.3%, 71.7% and 66.6% of isolates from pus, urine and sputum, respectively. Our observations were close to those of Seifi et al [15] who also reported that K. pneumoniae isolated from urine, sputum, blood and wound swabs were able to produce biofilm. Detection of biofilm formation even in the isolates originated from OPDs in the present study indicates that K. pneumoniae has the capacity to form biofilm not only on the medical devices used in the hospitalized patients but also directly on the host tissues.…”
Section: Discussionsupporting
confidence: 92%
“…pneumoniae with the ability to adhere, multiply and persist on inanimate surfaces in the hospital environment has been reported as a significant cause of severe nosocomial infections. Biofilm is the most vital virulence factor in the pathogenesis of this organism [15]. In the present study, we have demonstrated, for the first time, the prevalence of biofilm formation by K. pneumoniae isolated from OPDs and IPDs of tertiary care center of Nepal and their correlation with the antimicrobial resistance pattern.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…are among the most frequently isolated bacteria from burning wounds [2]. This organism is one of the most important opportunistic pathogens, causing hospital-acquired and healthcare-associated infections worldwide [3]. In recent decades, due to its tendency to develop antibiotic resistance and increasing virulence factor, lead to emerging this bacterium as clinically important organism [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Yang and Zhang (2008) reported the among 150 clinical sample of K. pneumoniae , the 44.7% biofilm formers, 45.3% of them produced ESBLs [29]. Other study indicated all K. pneumoniae isolated from sputum and surgicalwound swabs produced biofilms [30].…”
Section: Resultsmentioning
confidence: 97%